CSR Reporting Under Scrutiny - Goetmaeckers, Margot; Ryška, Tomáš, 1976-; Tyll, Ladislav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
Corporate social responsibility (CSR) has been a significantly present topic from a business as well as an academic perspective, resulting in the demand for CSR reporting. The demand for CSR reports comes from organizations’ stakeholders, claiming for more transparency and accountability. In particular, the number of reports concerning corporate social performances has become more readily due to the increased attention of businesses concerning social disclosure. Therefore, this research is investigating the status quo concerning organizations’ CSR reports in Belgium and France. The investigation is conducted through a profound literature review, followed by an explorative, cross-national comparative analysis. The insights suggest that organizations in the two countries are aware of the present tools available regarding CSR disclosure. However, issues concerning accountability, transparency, and evaluation of CSR performances still appear in the reporting practices.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses